A STUDY OF ADOLESCENTS’ ANXIETY AND ACHIEVEMENT IN ENGLISH AS A FOREIGN LANGUAGE - Fadillah, Ridha (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2010)
This paper aims at investigating whether there is relationship between students’ anxiety and students’ achievement in English as a foreign language among adolescents at Sekolah Menengah Umum Negeri 1 Banjarbaru, South Kalimantan. The sample was 152 students of sixteen and seventeen years old at second grade. The results indicate that the students’ anxiety in learning English as foreign language is at moderate level. There is no significant relationship between English language anxiety and students’ achievement in English as a foreign language as a whole. But a significant negative correlation between test anxiety and students’ achievement is indicated. And the difference of English language anxiety between male and female occurred on communication apprehension, it shows that female is more apprehensive than male in English communication but for overall anxiety, there is no difference in English language anxiety by gender at second grade in this school.